The Influence of Competence and Work Discipline on Employee Performance at the Regional Public Company (Perumda) Tirta Intan Drinking Water, Garut - Budiman; Ghassani Nur Shabrina; Irfan Rizki Gumilar (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Every company needs quality human resources because human resources play a key rolein supporting the company's success and growth. Quality human resources are those whohave the skills, knowledge and experience necessary to carry out their duties andresponsibilities well. The locus of this research is the Tirta Intan Garut Regional PublicCompany for Drinking Water, which is one of the Garut Regency BUMDs. This research ismotivated by the still not optimal performance of company employees, which is thought to beinfluenced by inadequate competence and low work discipline. The research aims todetermine the influence of competency and work discipline on employee performance atPerumda Air Minum Tirta Intan Garut. The research uses descriptive and associativeapproaches. The sample used in this research was 87 respondents who were employees ofPerumda Air Minum Tirta Intan Garut. Primary data was collected using a questionnairefilled out by 87 employees of Perumda Air Minum Tirta Intan Garut. The data analysis usedis Partial Least Square-Structural Equation Modeling (PLS-SEM) version SmartPLS 3.2.9.The research results show that competence and work discipline have a positive andsignificant effect on employee performance